Inesyvo ir adesyvo formų kilmės ir raidos klausimu - Rosinas, Albertas (Baltistica, 2000)
On the basis of the data collected from Lithuanian old manuscripts and the method of internal reconstruction the article presents a new interpretation of the origin and evolution of inessive and adessive forms: 1. The adessive singular developed not from the syntactic construction locative + pi, as was maintained earlier, but from the syntactic construction SV(stative verb) + dative + *prei which was a positional variant of the adessive construction SV + *prei + dative and met all the requirements of symmetry, cf. the allative constructions DV (dynamic verb) + *prei + genitive and DV + genitive + *prei. 2. The inessive singular derived from locatives + *en as a necessity to polarize the dative singular and the locative singular. As the dative plural and the locative plural were sufficiently polarized (cf. dat. *mōs (>-mus) and loc. -su), the old locative in -su was not replaced by any innovation, which is evident from the textual data of Mažvydas, Vilentas, Bretkūnas and other authors. 3. With the formation of the adessive singular from the construction dative + *prei and the inessive singular from locative + *en, the basis chosen for the adessive plural was not the dative plural (as is required by the principle of symmetry), but the old locative in -su; its choice was caused by the use of phonetically coincident dative and locative forms in inessive singular and adessive singular constructions. 4. The inessive plural forms in -sę (>-se, -si) are but transforms of the old locative in -su on the model of the inessive singular in -ę<*en, whereas the adessive plural form in -semp is a transform of an older adessive form in -su(m)p on the *-sen >sę model. It is a natural process of the morphemic levelling of inflections which took place in all the dialects at different times. The data drawn from the old manuscripts and the dialect sources attest to the following: 1) the inessive plural in -sę (>-se, -si) and the adessive plural in -semp are innovations; 2) the inessive plural in -sę (>-se, -si) did not develop from accusativeplural + *en, and the adessive plural was not formed from the new inessive in *en + pi.